Duckweed: a starch-hyperaccumulating plant under cultivation with a combination of nutrient limitation and elevated CO2 - Guo, Ling; Fang, Yang; Wang, Songhu; Xiao, Yao; Ding, Yanqiang; Jin, Yanling; Tian, Xueping; Du, Anping; Liao, Zhihua; He, Kaize; Chen, Shuang; Zhao, Yonggui; et al. (Frontiers in Plant Science, 2025)
IntroductionThe increasing global demand for starch has created an urgent need to identify more efficient and sustainable production methods. However, traditional starch sources, such as crop-based options, experience significant bottlenecks due to limitations in land use, water consumption, and the impacts of climate change. Therefore, there is a pressing need to explore and develop new sources of starch.MethodsWe develop a novel duckweed cultivation technology that combines nutrients limitation and CO2 supplementation to achieve very high starch content. In this study, we integrated whole-genome sequencing, epigenomics, transcriptomics, enzyme activity, and composition variation to elucidate the mechanisms of efficient starch accumulation in duckweed in terms of starch accumulation and carbon partitioning, regulation of the expression of genes in the starch metabolic pathway, and sucrose biosynthesis and transportation.Results and discussionAlthough Landoltia punctata exhibits dramatic gene family contraction, its starch content and productivity reached 72.2% (dry basis) and 10.4 g m-2 d-1, respectively, in 10 days, equivalent to a yield of 38.0 t ha-1 y-1, under nutrient limitation treatment with elevated CO2 levels. We also examined the mechanism of high starch accumulation in duckweed. This phenomenon is associated with the regulation of DNA methylation and transcription factors as well as the significantly upregulated transcription levels and the increased activities of key enzymes involved in starch biosynthesis. Moreover, while nitrogen redistribution was increased, sucrose biosynthesis and transportation and lignocellulose biosynthesis were reduced. These alterations led to a reduction in lignocellulose and protein contents and ultimately an increase in the accumulation of starch in the chloroplasts.ConclusionThis work demonstrates the potential of duckweed as a highly efficient starch producer.